Synthesis and pharmacological evaluation of newly detected synthetic cannabinoid receptor agonists AB-4CN-BUTICA, MMB-4CN-BUTINACA, MDMB-4F-BUTICA, MDMB-4F-BUTINACA and their analogs - Sparkes, Eric; Boyd, Rochelle; Chen, Shuli; Markham, Jack W.; Luo, Jia Lin; Foyzun, Tahira; Zaman, Humayra; Fletcher, Charlotte; Ellison, Ross; McGregor, Iain S.; Santiago, Marina J.; Lai, Felcia; et al. (Frontiers in Psychiatry, 2022)
Synthetic cannabinoid receptor agonists (SCRAs) continue to make up a significant portion new psychoactive substances (NPS) detected and seized worldwide. Due to their often potent activation of central cannabinoid receptors in vivo, use of SCRAs can result in severe intoxication, in addition to other adverse health effects. Recent detections of AB-4CN-BUTICA, MMB-4CN-BUTINACA, MDMB-4F-BUTICA and MDMB-4F-BUTINACA mark a continuation in the appearance of SCRAs bearing novel tail substituents. The proactive characterization campaign described here has facilitated the detection of several new SCRAs in toxicological case work. Here we detail the synthesis, characterization, and pharmacological evaluation of recently detected SCRAs, as well as a systematic library of 32 compounds bearing head, tail, and core group combinations likely to appear in future. In vitro radioligand binding assays revealed most compounds showed moderate to high affinity at both CB1 (pKi = < 5 to 8.89 ± 0.09 M) and CB2 (pKi = 5.49 ± 0.03 to 9.92 ± 0.09 M) receptors. In vitro functional evaluation using a fluorescence-based membrane potential assay showed that most compounds were sub-micromolar to sub-nanomolar agonists at CB1 (pEC50 = < 5 to 9.48 ± 0.14 M) and CB2 (pEC50 = 5.92 ± 0.16 to 8.64 ± 0.15 M) receptors. An in silico receptor-ligand docking approach was utilized to rationalize binding trends for CB2 with respect to the tail substituent, and indicated that rigidity in this region (i.e., 4-cyanobutyl) was detrimental to affinity.